Management of cancer during pregnancy and current evidence of obstetric, neonatal and pediatric outcome: a review article. (18th January 2019) - Maggen, Charlotte; van Gerwen, Mathilde; Van Calsteren, Kristel; Vandenbroucke, Tineke; Amant, Frédéric
Abstract : The diagnosis of cancer during pregnancy imposes a medical-ethical dilemma in weighing the risks of both mother and child. Increasing awareness of the feasibility of chemotherapy during pregnancy results in more pregnant patients receiving treatment for cancer. Information on obstetric and pediatric outcome of these high-risk pregnancies is greatly needed to guide physicians in patient counseling. In this review we present reported evidence for the incidence, diagnostic options, therapeutic management, obstetric risks, and neonatal outcome when cancer treatment is initiated during pregnancy. Decision-making when a cancer is diagnosed in a pregnant patient should be multidisciplinary, always taking the patient's perspective into account. Cancer treatment during pregnancy is associated with low birth weight and preterm delivery, therefore frequent obstetric follow-up during oncological treatment in a specialized center is mandatory. Short-term clinical, cardiac, and cognitive outcome of children pre-natally exposed to cancer treatment is overall reassuring. Long-term follow-up of children is warranted to define the possible effect of pre-natal cancer treatment on general health, fertility outcome, and the risk of secondary cancers.